Sol-gel grown aluminum/gallium co-doped ZnO nanostructures: Hydrogen gas sensing attributes. (April 2018) - Al-Asedy, Hayder J.; Bidin, Noriah; Al-khafaji, Shuruq A.; Bakhtiar, Hazri
Abstract: Aluminum (Al) and Gallium (Ga) co-doped ZnO nanostructures (AGZO NSs) were prepared on p-type Si(100) substrate using sol-gel united spin coating method. Ga contents were varied from 1 to 5 at% at fixed Al doping (1 at%). Synthesized samples were annealed at 500 °C for 3 h. The structural, morphological, and electrical property of the optimum sample (containing 3 at% of Ga) were determined. Optimum AGZO NSs enclosing highest density of nanorod (NR) arrays were selected to fabricate a hydrogen gas (H2 ) sensor. As-grown AGZO NSs revealed hexagonal wurtzite structure with mean grain size ≈ 41.20 nm and resistivity ≈ 0.6475 × 10 −2 Ω cm. The gas sensing attributes of the developed sensor was evaluated for two different temperatures (at 100 and 150 °C) under varying gas H2 contents (from 250 to 1750 ppm). Furthermore, the selectivity of the AGZO NSs for three different gases such as H2, CO and CH4 were examined. The sensitivity of the sensor at 100 °C was augmented sharply from 60% to 385% with the increment of H2 gas contents from 250 to 1750 ppm. This enhancement was attributed to the increases of hydrogen gas current (IH ) and good stability of the air atmosphere. The synthesized AGZO NSs have high potential for gas sensing, photovoltaic and field emission applications. Highlights: AGZO films were prepared using sol-gel united spin coating method. Prepared AGZO NSs revealed good crystallinity and low resistivity. Optimum AGZO film with vertically aligned nanorods was used to design hydrogen gas sensor. Such combined method is useful to control the growth of AGZO NSs with desired features.